Incidence of death and its predictors among neonates admitted with sepsis in referral hospitals, northwest Ethiopia, a prospective cohort study - Abiy, Saron Abeje; Animut, Yaregal; Ambaw, Worku Mequannt; Aragaw, Getie Mihret; Rade, Bayew Kelkay (Frontiers in Pediatrics, 2023)
Abstract Background: Each year, approximately 2.7 million neonates die in their first month of life worldwide, and the majority of these deaths occur in low-income countries. According to the Global Burden of Disease estimation, 1.3 million annual incident cases of neonatal sepsis were reported worldwide, resulting in 203,000 sepsis-attributable deaths. Little is known about the time to death of neonates and predictors after admission with a diagnosis of sepsis. This study aimed to assess the incidence and predictors of death among neonates admitted to the neonatal intensive care unit with a diagnosis of sepsis in referral hospitals in Northwest Ethiopia. Methods: A multicenter prospective follow-up study was conducted from November 11 to December 7, 2021. A stratified random sampling technique was employed to select 412 neonates. Neonates admitted with sepsis were followed until they develop event for a maximum of 28 days of age. A face-to-face interview was conducted with the mother of the neonate using a pretested and structured questionnaire, and neonatal charts were reviewed to collect baseline factors. Data were entered into Epi-data version 4.6 and exported to STATA version 14 for analysis. A multivariable exponential Cox regression model was fitted to identify predictors of death. Results: A total of 75 (18.47%) neonates died during the study period, with a 95% CI of 14.82–22.60. The incidence rate of death was 28 (95% CI, 22, 35) per 1000 person-days of observation, with a total follow-up time of 2677 person-days of observation. Birth weight (2500 grams) (AHR = 2.12, 95% CI: 1.01, 4.43), prematurity(AHR=2.06, 95% CI: 1.02, 4.15), duration of labor>24hrs(AHR=3.89, 95% CI: 1.38, 11.01), breast feeding(AHR = 0.43, 95% CI: 0.23, 0.80), having respiratory distress syndrome (AHR = 1.77, 95% CI: 1.02, 306), oxygen saturation less than 90% (AHR = 2.23, 95% CI: 1.02, 306) were significant predictors of death among neonates admitted with sepsis. Conclusion and recommendation: The incidence of neonatal mortality in this study was high. Early detection and appropriate management of patients’ presentations like respiratory distress syndrome and low oxygen saturation are necessary to reduce neonatal sepsis-related mortality.